The Influences of Local Language to Students in Learning English - Robi Soma (Global Expert: Jurnal Bahasa dan Sastra, 2018)
AbstractIt is universally believed that learning a foreign language has its own difficulties. This paper discusses some problems which are faced by English as a Foreign Language students in learning English. Those problems can come from the students themselves and it can also come from their environment that have strong influence their success in learning a foreign language, in this case English. Moreover, how students’ local language influence them in learning English and how to overcome such an obstruction are also discussed here.Keyword : local languages, English, and foreign language learning AbstrakSecara universal diyakini bahwa mempelajari bahasa asing memiliki kesulitan tersendiri. Makalah ini membahas beberapa masalah yang dihadapi oleh Inggris sebagai siswa Bahasa Asing dalam belajar bahasa Inggris. Masalah-masalah itu bisa berasal dari para siswa itu sendiri dan itu juga bisa berasal dari lingkungan mereka yang memiliki pengaruh kuat terhadap keberhasilan mereka dalam mempelajari bahasa asing, dalam hal ini bahasa Inggris. Selain itu, bagaimana bahasa lokal siswa mempengaruhi mereka dalam belajar bahasa Inggris dan cara mengatasi hambatan semacam itu juga dibahas di sini.Kata kunci : bahasa lokal, bahasa Inggris, dan pembelajaran bahasa asing